Enhanced Skin Incisional Wound Healing With Intracellular ATP Delivery via Macrophage Proliferation and Direct Collagen Production - Harshini Sarojini; Alexander Bajorek; Rong Wan; Rong Wan; Jianpu Wang; Qunwei Zhang; Adrian T. Billeter; Sufan Chien (Frontiers Media S.A., 2021)
This study sought to use a newly developed intracellular ATP delivery to enhance incisional wound healing to reduce surgical wound dehiscence and to explore possible mechanism for this effect. Thirty-five adult New Zealand white rabbits were used. Skin incisions were made on the back and closed. ATP-vesicles were mixed with a neutral cream for one side of the wounds while the neutral cream alone was used on the other side of the wounds. Laser speckle contrast imaging (LSCI), biomechanical, histological, and immunohistochemical analyses were performed 7 and 14 days after surgery, and macrophage culture was used to test the enhanced collagen production ability. Among them, 10 were used for wound perfusion study and 25 were used for wound biomechanical and histological/immunohistochemical studies. Wound tissue perfusion was reduced after surgery especially in early days. Wound tissue tensile strength, breaking stress, and elasticity were all much higher in the ATP-vesicle treated group than in the cream treated group at days 7 and 14. The healing was complemented by earlier macrophage accumulation, in situ proliferation, followed by direct collagen production. The results were further confirmed by human macrophage culture. It was concluded that intracellular ATP delivery enhanced healing strength of incisional wounds via multiple mechanisms.